Bioprotective potential of lactic acid bacteria - Laslo É.; György É.; András Cs. D. (Acta Universitatis Sapientiae: Alimentaria, 2020)
Acidification in lactic-fermented foods is realized by lactic acid bacteria as an added starter culture or by autochthonous strains. These microbial strains possess different prominent features that define the technological, organoleptic, nutritional, and microbial safety aspects of the product. The bioprotective effect of the bacterial strains may be related to antagonistic properties against food spoilage and/or pathogenic strains. The aim of the present study is to determine the antimicrobial properties of three different food-grade lactic acid bacteria in order to use them as bioprotective cultures. Our findings show that the Lactobacillus pentosus, Enterococcus faecalis, and Pediococcus parvulus exerted a bacteriostatic effect on Escherichia coli and Bacillus cereus, whereas the Saccharomyces cerevisiae growth was not inhibited, which made them susceptible agent for co-culture systems.